The burden of cervical cancer in Vietnam: Synthesis of the evidence. (April 2019) - Thi Nguyen, Diep Ngoc; Simms, Kate; Vu Nguyen, Huy Quoc; Van Tran, Thuan; Nguyen, Nga Hoai; LaMontagne, D. Scott; Castle, Philip; Canfell, Karen
Highlights: Data on cervical cancer incidence and mortality are limited in Vietnam. Two cancer registries have been reported by the International Agency for Research on Cancer, which cover only urban populations representing ∼20% of the national population. Cervical cancer incidence varies between Hanoi (North) (ASR = 6.7/100, 000 [1993–1997]) and Ho Chi Minh City (South) (28.8/100, 000 [1995–1998] and 14.1/100, 000 [2009–2012]). Without any further intervention, the number of new cases will increase from 6930 in 2012 to 8562 in 2049, giving a total of ∼400, 000 new cases over the period 2012–2049. These findings could be used as background information prior any interventions of cervical cancer in Vietnam, and support similar initiatives in other low- and middle-income countries. Abstract: There is currently no national cervical screening or HPV immunization program in Vietnam. This study aims to synthesize available data on the burden of disease and to project the burden of cervical cancer to 2049 if no major interventions are implemented. We reviewed published data sources on risk factors for HPV prevalence, high-grade lesions, cervical cancer incidence and mortality in Vietnam from 1990 to 2017. We then used the available data to project the number of new cervical cancer cases for the period 2013–2049. Data on cervical cancer incidence and mortality in Vietnam are limited; two Vietnamese cancer registries have been reported on by the International Agency for Research on Cancer, which cover urban populations representing ∼20% of the national population. The reported age-standardized cervical cancer incidence in Hanoi was 6.7 (1993–1997), compared to 28.8 and 14.1 per 100, 000 women in Ho Chi Minh City (1995–1998 and 2009–2012, respectively). Cancer mortality data are not uniformly available from cancer registries or mortality surveys in Vietnam because cause of death has not been routinely ascertained. Based on available urban population registry data, estimated rates in the rural population, and forward projection of existing trends, we estimate that without any further intervention, the number of new cases will increase from 6930 (range 5671–8493) in 2012 to 8562 (range 5775–12, 762) in 2049, giving a total of 379, 617 (range 276, 879–542, 941) new cases over the period 2013–2049. These findings help underpin the case for the delivery of HPV vaccination and cervical screening in Vietnam, and support similar initiatives in other low- and middle-income countries.